Efeito da oxigenação hiperbárica na expressão dos genes glutationa peroxidase 4 e Lactoperoxidase no pulmão de camundongos isogênicos após lesão de isquemia e reperfusão em intestino delgado - Ikejiri, Adauto Tsutomu [UNIFESP] (2017)
Objective: determine the effect of hyperbaric oxygenation on Glutathione peroxidase 4 (Gpx4) and Lactoperoxidase (Lpo) genes expression in mice lung tissue subjected to ischemia and reperfusion intestinal (IRI). Methods: thirty isogenic male mice (C57BL/6) were randomly distributed into five groups: the control group (GC) with animals to anesthesia, laparotomy and observation of 120 minutes; ischemia and reperfusion Group (GIR), submitted to anesthesia, laparotomy, ischemia of small intestine for 60 minutes and 60 minutes of reperfusion. Three groups were treated with Hyperbaric Oxygenation (OHB) in distinct periods: during ischemia (GOHB + I), during the reperfusion (GOHB + R) and during ischemia and reperfusion (GOHB + IR). A sample set of six animals from each group was subjected to reverse transcription and quantitative polymerase chain reaction (RT-qPCR) in real-time for determining the oxidative stress and antioxidant defense. All the genes that were hyper expressed or hypo expressed more than three times the allowed limit by the algorithm [2-ΔΔCt] found to be biologically relevant. Results: our data show that among the 84 genes in the lungs related to oxidative stress, two genes (Gpx4 and Lpo) were hyper expressed, showing a clear relationship of these genes with the pulmonary oxidative stress. When these genes are subjected to treatment with OHB there is a clear decrease in its expression in the group GOHB+I. Conclusions: the IRI promotes the hyper expression response from Gpx4 and Lpo genes in lung tissue related to the antioxidant response to oxidative stress. OHB treatment showed to be associated with decreased expression of these antioxidant genes, demonstrating a reduced need of antioxidant response, suggesting its beneficial effect on the mechanism of pulmonary oxidative stress when applied during ischemia.